Government Strategies in Responding to the Economic Resilience of Families of Ex-Migrant Workers from the Perspective of Ultimate Justice - Enny Puji Lestari; Royhatul M’wa Hr; Dalila Afiyah Senegal (Journal of Islamic Mubadalah, 2024)
This article analyzes the economic resilience of former migrant worker families in East Lampung Regency. Former migrant workers have assets in the form of capital, but are often poorly organized, which creates challenges, including the double burden they face. The purpose of this article is to analyze what is the government's strategy in responding to the economic resilience of migrant worker families from the perspective of intrinsic justice? The analysis method is carried out qualitatively using the theory of intrinsic justice; Phenomenological approach; The object of research was carried out in East Lampung Regency; Primary data sources through mapping of former migrant workers. Data collection through observation, interviews and documentation. The results of the study found that the participation of former migrant workers in decision-making and utilization of empowerment programs is still limited. The majority of former migrant workers are women (74% or 347 people). Intrinsic justice in migrant worker families is a major concern so that there is no bias in everyday life. The government's strategy is also still limited to providing pre-departure access and provision, but has not been optimal in post-return assistance for sustainable economic empowerment. The contribution of this research requires a comprehensive strategy from the government that is just through sustainable assistance that pays attention to the specific needs of former migrant women in an effort to achieve family economic independence.